2011
DOI: 10.1126/science.1202723
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 Promotes DNA Repair Under Stress by Activating PARP1

Abstract: SIRT6 is a mammalian homolog of the yeast Sir2 deacetylase that promotes longevity in yeast and invertebrates. Mice deficient for SIRT6 exhibit premature aging and genome instability. Here we show that in mammalian cells subjected to oxidative stress SIRT6 is recruited to the sites of DNA double-strand breaks (DSBs) and strongly stimulates both pathways of DSB repair, nonhomologous end joining and homologous recombination. We found that SIRT6 physically associates with PARP1 leading to stimulation of PARP1 pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
769
3
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 759 publications
(793 citation statements)
references
References 35 publications
14
769
3
7
Order By: Relevance
“…Accordingly, 53BP1 deletion in BRCA1‐deficient cells allows replication protein A (RPA) loading and restoration of HR. A previous report suggested that SIRT7 may regulate HR repair (Mao et al , 2011). However, the absence of SIRT7 did not lead to a detectable change of HR levels, as measured by RAD51 focus formation (Appendix Fig S5A–C), by measuring SCE events, or by using a HR reporter locus (Appendix Fig S7C–G).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, 53BP1 deletion in BRCA1‐deficient cells allows replication protein A (RPA) loading and restoration of HR. A previous report suggested that SIRT7 may regulate HR repair (Mao et al , 2011). However, the absence of SIRT7 did not lead to a detectable change of HR levels, as measured by RAD51 focus formation (Appendix Fig S5A–C), by measuring SCE events, or by using a HR reporter locus (Appendix Fig S7C–G).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to investigate whether PARP activity affects SIRT7‐mediated transcriptional regulation such as the regulation of ribosomal gene expression. On the other hand, SIRT6‐mediated mono‐ADP ribosylation of PARP1 enhances its activity as a DNA repair mediator (Mao et al , 2011). Our results suggests that PARP proteins, at least at the level of DNA repair, are acting upstream of SIRT7 (Fig 6F and G).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pretreatment with heat shock resulted in improved DNA repair in yeast [50]. More generally, sirtuin protein (SIRT6) has recently been shown to stimulate DNA repair in cells under increased oxidative stress [51]. This multifunctional protein is a member of sirtuin family of proteins that play a key role in regulating metabolism, lifespan (but see Burnett et al [52]), chromosomal stability and stress response across taxa [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Among the gene targeting models for seven mammalian sirtuins, SIRT6-deficient mice displayed a prominent premature aging phenotype accompanied by shortened life span (12,13). SIRT6 has been demonstrated to regulate longevity by a variety of mechanisms, including NF-kB inhibition, base excision repair, homologous recombination, and modulation of insulin-like growth factor (IGF)-I signaling (13)(14)(15)(16)(17)(18). Although IGF-I signaling has been reported to be involved in autophagy and cellular senescence (19), autophagy modulation by SIRT6 and implication of SIRT6 in regulation of cellular senescence during COPD pathogenesis remain to be elucidated.…”
mentioning
confidence: 99%